Mechanism of Sulfur Poisoning and Storage: Adsorption and Reaction of SO2 with Stoichiometric and Reduced Ceria Films on Cu(111) - Happel, Markus; Lykhach, Yaroslava; Tsud, Nataliya; Skala, Tomas; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Physical Chemistry C, 2011)
We have performed a systematic synchrotron radiation photoelectron spectroscopy (SR-PES) study of the interaction of SO2 with stoichiometric CeO2(111) and reduced CeO2-x films supported on Cu(111). Resonant photoelectron spectroscopy (RPES) was utilized to monitor changes in the cerium oxidation states. Adsorption of SO2 at 150 and 300 K results mostly in formation of sulfite (SO32-) species on both reduced and stoichiometric ceria. Other species such as sulfate (SO42-), SO2 chemisorbed at cationic sites, anionic SO2-, atomic sulfur, surface sulfides, and bulk oxy-sulfides were detected. The origin of these species is discussed in relation to the changes in the oxidation state of ceria cations at the surface. The thermal evolution of the species formed upon adsorption at 150 and 300 K was studied systematically on both the stoichiometric and the reduced films. It was found that the sulfite partially desorbs to release SO2 and partially decomposes. In general, the reduced CeO2-x surface was found to be much more active toward cleavage of S-O bonds, as indicated by a higher amount of oxy-sulfide species produced. The decomposition pathways can be monitored via changes of the ceria oxidation state and are discussed in relation to the stoichiometry of the ceria surface.